Central nervous system infection due to Cryptococcus gattii sensu lato in India: Analysis of clinical features, molecular profile and antifungal susceptibility. Issue 11 (23rd July 2017) - Lahiri Mukhopadhyay, Shayanki; Bahubali, Veenakumari H.; Manjunath, Netravathi; Swaminathan, Aarthi; Maji, Sayani; Palaniappan, Marimuthu; Parthasarathy, Satishchandra; Chandrashekar, Nagarathna
Summary: Cryptococcus gattii species complex has evolved as a pathogen in the last two decades causing infection among both immunocompetent and immunocompromised hosts. We aimed to analyse the clinical features of CNS infection caused by C. gattii sensu lato, molecular and antifungal susceptibility profile of this pathogen. Cases diagnosed to have CNS cryptococcosis were included in the study. Cryptococcus recovered from patient's specimen was identified by standard protocol. Species confirmation, mating type and molecular type determination were performed by PCR based methods. Antifungal susceptibility was tested in VITEK2C to amphotericin B, 5‐flucytosine, fluconazole and voriconazole. Among 199 cases, 20 (10%) were due to C. gattii, comprising of 75% cryptococcal meningitis and 25% cryptococcoma cases. Young adult males were commonly affected. Headache and vomiting were prominent symptoms and 50% were immunocompromised. Among the isolates, 75%, 20% and 5% were C. tetragattii, C. gattii sensu stricto and C. bacillisporus respectively and all had mating type α. Four (20%) isolates of C. tetragattii and the only isolate of C. bacillisporus were resistant to fluconazole. The most common species isolated from south India is C. tetragattii . The study contributes to the epidemiology of C. gattii and reiterates the need for genotyping and antifungal susceptibility testing.